2017
DOI: 10.1002/smtd.201700260
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Fast Synthesis of Few‐Layer Black Phosphorus via Microwave‐Assisted Liquid‐Phase Exfoliation

Abstract: High‐quality, few‐layer black‐phosphorus (BP) flakes are prepared in a common organic solvent with very short processing times using microwave‐assisted liquid‐phase exfoliation. A comprehensive range of analysis, combined with density‐functional theory calculations, confirms that the product prepared using the microwave technique is few‐layer BP with small‐ and large‐area flakes. The suspended exfoliated BP sheets show excellent stability, while samples dispersed onto silicon from the suspensions exhibit low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 40 publications
11
59
0
Order By: Relevance
“…Three main characteristic peaks at around 220, 300, and 370 nm were observed (Figure b). These three strong and sharp peaks are very consistent with previously reported theoretical results and the spectrum of mechanically exfoliated phosphorene . Recently, we reported the preparation of high‐quality few‐layer black phosphorus in N ‐Methyl‐2‐pyrrolidone (NMP) using a novel microwave‐assisted LPE method .…”
Section: Detailed Pv Parameters Of the Pscs Fabricated Based On Tio2‐supporting
confidence: 90%
See 3 more Smart Citations
“…Three main characteristic peaks at around 220, 300, and 370 nm were observed (Figure b). These three strong and sharp peaks are very consistent with previously reported theoretical results and the spectrum of mechanically exfoliated phosphorene . Recently, we reported the preparation of high‐quality few‐layer black phosphorus in N ‐Methyl‐2‐pyrrolidone (NMP) using a novel microwave‐assisted LPE method .…”
Section: Detailed Pv Parameters Of the Pscs Fabricated Based On Tio2‐supporting
confidence: 90%
“…These three strong and sharp peaks are very consistent with previously reported theoretical results and the spectrum of mechanically exfoliated phosphorene . Recently, we reported the preparation of high‐quality few‐layer black phosphorus in N ‐Methyl‐2‐pyrrolidone (NMP) using a novel microwave‐assisted LPE method . In these studies, we have shown for the first time the benchmark UV–vis spectra for the solution processed phosphorene, highlighting the three major peaks, which are in excellent agreement with the peaks observed for the VFD‐exfoliated phosphorene solution.…”
Section: Detailed Pv Parameters Of the Pscs Fabricated Based On Tio2‐supporting
confidence: 89%
See 2 more Smart Citations
“…d,e) Reproduced with permission. [37] l,m) HR-TEM of BPQDs with different lattice fringes. f) Cross-sectional TEM and g) HR-TEM image with selected area electron diffraction pattern (inset) of BP thin films prepared using PLD.…”
Section: Introductionmentioning
confidence: 99%